ANALISIS KESALAHAN BAHASA INDONESIA PADA MEDIA SOSIAL - Dewi Naluri Afriyanti; Oktavia, Yunisa (eScience Humanity Journal, 2023)
Indonesian is the most effective language used in communication. Language has a very important role when conveying information. In the communication process, the obstacle that often occurs in the communication process is the lack of language skills. Usually, the form of language skills is due to language errors. These language errors are very common in our environment, namely errors in newspapers, magazines, banners, television, social media, theses, and so on. The method used in this study is a qualitative method. Which aims to explain a phenomenon in depth and is carried out by collecting data as depply as possible. What is meants by the descriptive method is a pr. The results of this study found many writing errors that were not based on Indonesian spelling guidelines. Of course, the error is found on social media, namely writing errors on gojek, instagram, where the writing does not use capital letters.